Pigment epithelium-derived factor as a natural matrix metalloproteinase inhibitor: a comparison with classical matrix metalloproteinase inhibitors used for cancer treatment - Alcantara, M.; Dass, Crispin (John Wiley & Sons Ltd., 2014)
Objectives: In the 1990s, the discovery of the important role of matrix metalloproteinases (MMPs) in cancer angiogenesis, growth and metastasis galvanised research efforts to search for ways to inhibit these MMPs. To date, this has resulted in the investigation of approximately 50 MMPIs which have undergone various phases of clinical trials. However, despite a large body of research being devoted to discovery and development of MMPIs, results have largely not been supportive of this approach to anticancer treatment. Key findings: The reasons for the general failure of these drugs in clinical trials include various unwanted side-effects, the use of healthy volunteers to provide drug dosages which did not correctly reflect dosages for cancer patients, and the exclusion of patients with early stage cancer in clinical trials despite MMPs being determined to be critical for the angiogenic switch, a process associated with early tumour growth. In contrast, a naturally-occurring endogenous protein and a non-functional serine protease inhibitor (serpin), pigment epithelium-derived factor (PEDF), has been proposed for cancer therapy partly due to its ability to regulate specific MMPs central to cancer progression. Summary: PEDF has been found to specifically downregulate membrane-type I matrix metalloproteinase (MT1-MMP) and furthermore, potentially matrix metalloproteinase-2 (MMP-2), two of the most commonly implicated MMPs in neoplasia.